The Influence of a Hedonistic Lifestyle, Consumptive Behavior and the Importance of Financial Literacy on Students' Personal Financial Management Asmadewa Dormitory Yogyakarta - Panu, Yosefa Renan (INVOICE : JURNAL ILMU AKUNTANSI, 2024)
This research aims to examine and analyze the influence of hedonic lifestyle and consumer behavior on students' personal financial management, taking into account the importance of financial literacy. Hedonic lifestyles, which reflect an orientation toward instant pleasure and gratification, as well as consumerist behavior, characterized by the tendency to spend money impulsively and unplanned, have become a focus of attention in the study of personal finance. This study explores how consumer behavior and hedonic lifestyles can influence students' ability to manage their own finances. The research population consisted of 100 students living in the Asmadewa dormitory in Yogyakarta. From this population, 53 respondents were selected as samples using the Non-Probability Sampling method. Data was collected through a questionnaire that assessed hedonic lifestyle, consumer behavior, financial literacy and personal financial management. The results of the analysis show that hedonic lifestyle and consumer behavior have a significant positive influence on students' personal financial management. These findings highlight that students who tend to have a hedonic lifestyle and higher consumer behavior tend to face challenges in managing their own finances. Although financial literacy does not directly influence students' personal financial management in the context of this research, the importance of financial literacy should not be overlooked. This study provides a better understanding of the factors that influence college students' financial decisions and underscores the need for comprehensive financial education in higher education settings. Thus, efforts to increase financial awareness and knowledge among students can help overcome the negative impact of hedonistic lifestyles and consumer behavior on their personal financial management.